Evaluating knowledge gaps in sea-level rise assessments from the United States - Garner, Andra J. (2023)
There have been many scientific advances regarding future sea-level projections, however it is unclear if these have been transferred to assessment reports used by stakeholders. Here, we present a first-of-its-kind comprehensive analysis of regional sea-level rise (SLR) assessments for the United States (U.S.). We identify variations in time horizons over which regions plan for SLR, with 25 projections from the U.S. Northeast and West that extend to 2150 or beyond, but no projections from the U.S. South beyond 2100. The majority of 2100 projections from the U.S. Northeast (77%) and West (83%) include ranges of future SLR, while 88% of projections from the U.S. South include only single estimates. At least 56% of U.S. communities in the database underestimate the upper end of future SLR compared to the regional projections of the Intergovernmental Panel on Climate Change Sixth Assessment Report.